Bridging Worlds with Words: Translanguaging Space as A Transformation of Specific-Cultural Constructs - Prasatyo, Bayu Andika; Luciana, Luciana; Hidayati, Dini (FKIP Universitas Lampung, 2025)
Bridging Worlds with Words: Translanguaging Space as A Transformation of Specific–Cultural Construct. Objectives: Translanguaging practices in multilingual contexts have emerged as a dynamic framework for understanding how learners utilize their linguistic repertoires to construct meaning and negotiate cultural identities. This study investigates the role of translanguaging spaces in shaping identity construction within English as a Foreign Language (EFL) classroom in Indonesia. The research explores how learners creatively and critically engage with their linguistic resources, leveraging translanguaging practices to express themselves, reform specific-cultural constructs, and navigate multilingual environments. Methods: The study employs a qualitative approach, focusing on narratives of identity construction through classroom performances. Methods include observations, interviews, and analysis of multimodal compositions created by multilingual EFL learners. Findings: It reveals that translanguaging fosters deeper engagement in meaning-making processes by enabling learners to draw on their sociocultural resources and linguistic repertoires. It highlights how translanguaging spaces facilitate the projection and negotiation of cultural identities, allowing learners to occupy social spaces that reflect their unique experiences. Conclusion: Conclusions emphasize the transformative potential of translanguaging practices in EFL education, demonstrating how they empower learners to reconstruct cultural identities while enhancing cognitive and linguistic flexibility. The research highlights the importance for pedagogical approaches that embrace translanguaging as a tool for fostering inclusivity, creativity, and critical thinking in multilingual classrooms. Keywords: cultural identity construct, EFL learners, translanguaging space, multilingual.